Geographic tongue (benign migratory glossitis) in a patient treated with Pazopanib for metastatic renal cell carcinoma. (2016) - Gilmore, Gregory; Qamar, Samina; Chaudhary, Uzair B.
Abstract: Significant advances in the last decade have been made in the management of patients with metastatic renal cell carcinoma (RCC) with targeted therapies, however the toxicities from these new agents are still being discovered. Vascular endothelial growth factor (VEGF) inhibitors and tyrosine kinase inhibitors (TKI) have been associated with many oral mucocutaneous toxicities including the development of Geographic Tongue (GT). We present the first reported case of GT in a 58 year old male patient being treated with Pazopanib as a monotherapy for metastatic RCC which resolved after cessation of the medication during an acute infection. However, GT is a benign condition that often does not require dose reduction or discontinuation of Pazopanib. Although it can be alarming to patients, treatment is focused on reassurance of the benign nature of the disease to patients and the ability to continue on treatment. This case illustrates the continued discovery of new toxicities during a time in which we are seeing rapid development of new therapies. We suspect GT is a class effect of VEGF inhibitors and TKIs due to their disruption of buccal mucosa homeostasis and although GT is considered rare it is likely underreported in the literature.